Effect of β-glucan on behavioral, biochemical and hematological parameters against toxicity of copper sulfate in common carp Cyprinus carpio L.: 1Jamal K. Al-faragi, 2Eqbal S. Najem, 1Sanaa A. Mustafa - Al-faragi, Jamal K. (The Iraqi Journal of Veterinary Medicine, 2014)
The aim of the present study was to assess the effect of a commercial ß-glucan against acute toxic effect of copper sulfate on common carp Cyprinus carpio L. behavioral, hematological parameters and biochemical tests. A total of 250 Fish (150 ± 2 g) were fed a basal control diet or the basal diet plus a ß-glucan (1 g kg-1 diet) for 60 days. LC50 was calculated for 72 h which was 10.83 mg L-1. At the end of the trial, CuSO4.5H2O was added to all treatments at a dose of 5 mgL-1 for T1 and T2, 7mg L-1 for T3 and T4, 9 mgL-1 for T5 and T6 for 96h. Fish behavioral changes were recorded during 96h of exposure to different Cu concentrations with and without β-glucan, which showed abnormalities such as increase swimming activity, jerky movement, loss of equilibrium, respiratory stress, increase operculum movement, frequent jumping, erratic swimming and swimming near the water surface. On the other hand, ß-glucan supplemented groups showed significant increase (P≤0.05) in Hb concentration, PCV%, RBC and WBC count in comparison with groups without ß-glucan. The results of dietary groups without ß-glucan showed a significant decrease (P≤ 0.05) in Hb concentration, hematocrit value, RBC count, but there were significant increase (P≤ 0.05) in WBC count with an increase of Cu concentration compared to control groups. Results showed significant increase (P≤ 0.05) in dietary groups without ß-glucan in values of ALT, AST and ALP enzymes activity with elevation of Cu levels compared to control group. But, ß-glucan supplemented groups showed significant decrease (P ≤ 0.05) in values of ALT, AST and ALP enzymes activity in comparison with dietary groups without ß-glucan. These results suggested that β-glucan has protective effect against CuSO4 toxicity and future studies should be pursued particularly immune response and molecular studies